PENERAPAN INTEGRATED MARKETING COMMUNICATION TOKO KOPI PADMA DALAM MENARIK PELANGGAN (The Commercium, 2023)
The trend of consuming coffee creates a contemporary business, namely coffeee shop. In this era, marketing communication that is often used is the Integrated Marketing Communication (IMC) Strategy. IMC is the concept of strategy in a business. The café that carries out marketing communications using IMC is Padma Coffee Shop. Coffe shop that carries an ancient or vintage theme takes the sub-name Padma Kopi Tjantik. This place is located in Surabaya. IMC combines various elements of corporate marketing communication in order to achieve optimal marketing results which states that the theory of Integrated Marketing Communication or IMC is a form of communication that is focused on planning, making, unifying, and implementing or implementing various forms of marketing communication. The purpose of IMC is either directly or indirectly, to influence potential customers to purchase products or use services. This research explains that Padma Coffee Shop applies five of eight aspects of IMC, including online advertising, namely Instagram Ads. Event and experience of opening and launching coffee shop. Aspects of public relations and publicity, public relations work is carried out by the owner by entering various coffee activist communities and expanding networks. Now Padma Coffee Shop is developing a website. At Padma Coffee Shop, all forms of online marketing communication and social media marketing are under coordination between the creative team and the owner. Then the personal selling aspect with the provision of testers. Keywords: IMC, Attract Customer